ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTEGRASI PASAR SPASIAL CABAI MERAH DI INDONESIA - Adana, Alif Haidir; Nauly, Dahlia; Pambudi, Renno Aji (Universitas Galuh, 2023)
Chili is one of the horticultural commodities that have high economic value and very volatile . Red chili production is concentrated on the islands of Sumatra and Java. When there is an imbalance in supply and consumption, it causes parts of Indonesia to have excess or shortage of red chili, which causes inter-provincial trade that causes market integration. The purpose of this study was to analyze the determinant of the red chili spatial market integration in Indonesia. The data used in this research was secondary data calculated using multiple regression analysis. The results of this study indicate that the factors that determine the spatial market integration of red chili in Indonesia are the population of the original province, the amount of red chili production in the province of destination, and the price of the fuel in the destination province.